The Influence Of Brand Truste And Service Quality On The Customer Satisfaction of Honda Motor Dealers (Study on Honda Motorcycle Users in Medan City) - M. Aditya Rifki Ginting; Nicholas Marpaung (SEAN Institute, 2023)
In customer satisfaction at Honda dealer Sisingamangaraja No. 362 Medan City in the realization that less than the maximum is also evidenced in the reviews given to the dealer is very much a low rating given customers Honda dealer Sisingamangaraja No. 362 City Terrain. This study aims to analyze the effect of brand trust on customer satisfaction at Honda motorcycle dealers, analyze the effect of service quality on customer satisfaction at Honda motorcycle dealers, and to analyze the effect of brand trust and service quality on customer satisfaction at Honda Motorcycle Medan dealers. The form of research used in this study is quantitative research with associative approach. Sampling is done through probability sampling technique and using 100 respondents as a sample. Data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis test. The results of this study show that brand trust does not significantly affect customer satisfaction. Meanwhile, service quality significantly affects customer satisfaction. However, brand trust and service quality, affect equally to Customer Satisfaction